The effect of enthalpy of mixing on the atomic level structure and plasticity of amorphous alloys: A molecular dynamics simulation study in a binary model system. (January 2018) - Yun, Y.S.; Kim, B.J.; Na, J.H.; Nam, H.-S.; Cha, P.-R.; Kim, W.T.; Kim, D.H.
Abstract: Molecular dynamics simulations were performed to investigate the effect of the enthalpy of mixing on the atomic level structure and plasticity of binary metallic glasses by using an ideal model potential. Whereas some model alloys with a strong positive enthalpy of mixing solidified into mixtures of microcrystalline domains of face-centered cubic or hexagonal close-packed crystal structures, the other alloys solidified into amorphous structures. Various structural properties of the amorphous alloys were analyzed as a function of the enthalpy of mixing interaction parameter. The deformation behavior of the amorphous samples was discussed in terms of atomic-level structural features such as the fraction of icosahedral clusters, the degree of short-range ordering and potential energies of atomic clusters in order to find a clue on the relationship between the mechanical properties and atomic structure of the amorphous alloys. Graphical abstract: Highlights: Atomic structures and plasticity of amorphous alloy models were characterized. The effect of enthalpy of mixing on amorphous alloy properties was analyzed. Our model presents how atomic structure affects the plasticity of amorphous alloys.